Paving the Path to Patient-Centered Healthcare in Africa: Insights From a Student Led Initiative - David Jolly Muganzi; Catherine Misango Namara; Timothy Mwanje Kintu; Linda Atulinda; Raymond Bernard Kihumuro; Bonaventure Ahaisibwe; Victor M. Montori (Ubiquity Press, 2024)
Patient-centered care (PCC) is a key domain of healthcare quality. Its importance is driven by evidence-based medicine, the predominance of chronic conditions requiring self-care, and the recognition of the priority of patient goals, values, priorities, and preferences in determining care plans. This article emphasizes the urgent need for Africa to develop PCC and a workforce committed to its implementation, as well as highlights an initiative by African medical students to champion PCC continent-wide. Embracing this transformative approach presents Africa with an unprecedented opportunity to improve care for each person. Through a comprehensive exploration of unique strategies and considerations in African health professions education, this viewpoint seeks to spark dialogue and inspire action towards a future where patient-centered care is the foundation of healthcare delivery in Africa.